(untitled) (Tanzania Medical Journal, 2020)
Background: Prostate cancer (PC) is a common health problem among men globally with high incidence and mortality. The mortality following PC is associated with advanced disease progressing to castrate resistance following androgen ablation therapies. While advances to address castrate resistant prostatic cancer (CRPC) have shown good results, the burden of castrate resistant cancer in Tanzania has remained unknown hence our patients cannot benefit from such advances. This study therefore aimed to determine the magnitude and clinical presentation among patients with a diagnosis of castrate resistant cancer at Muhimbili National Hospital in 2018-2019. Methods: This was a retrospective descriptive hospital based study carried out at Muhimbili National Hospital. Patients who were treated with androgen blockade, had evidence of attainment of castrate levels of testosterone with a diagnosis of castrate resistant prostate cancer were identified. Information regarding primary prostatic cancer treatment, clinical disease progression symptoms, and age of the patients were collected. Descriptive statistics were prepared and summarized as tables and figures. Results: We recruited 293 patients with prostate cancer treated by androgen deprivation therapy. Bilateral orchiectomy was the most common treatment modality offered for advanced PC. Castrate levels of testosterone were achieved in 189 (95.5%) of the patients who had testosterone levels checked. Ninety-Six (50.8%) had met the criteria for diagnosis of castrate resistant prostate cancer with mean age of 71.23±4.2 years. Patients presented with lower urinary tract symptoms and metastatic features. Most of the patients had a poorly differentiated histology with prostate specific antigen (PSA) over 100ng/l. Only 13.5% of the patients had spine magnetic resonance imaging (MRI) for their work up. Conclusion and recommendation: Half of patients treated for advanced PC at MNH will progress to castrate resistance following androgen deprivation therapy. More studies are needed to understand the predictors of CRPC and related treatment strategies. Key words: Castrate Resistant Prostate cancer, androgen deprivation therapy, advanced prostate cancer